2018
DOI: 10.1002/jssc.201800649
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly imprinted polymer based diffusive gradients in thin‐films for in situ selective sampling and determination of ciprofloxacin

Abstract: A technique of diffusive gradients in thin films with ciprofloxacin-molecularly imprinted polymers as the binding agent was developed for in situ selective sampling and measurement of ciprofloxacin in water. The ciprofloxacin uptake by the method increased linearly with time (r = 0.998) with a recovery of 96.8% in synthetic solution. The method performance was not dependent on solution pH over the pH range of 2-11 and ionic strength range from 1 × 10 to 0.5 mol/L sodium nitrate. The binding agent has a higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The highly polar aprotic solvent (ACN) is suitable for preparing of CIP imprinted polymers. 19,24 In contrast, the polar protic solvent (methanol) reduces the imprinted polymer selectivity due to their competitive interaction with MAA via hydrogen bond. 19 Moreover, the MIPs synthesized in highly polar solvents have small particles (<2 mm) for SPE applications.…”
Section: Synthesis Of Imprinted Polymersmentioning
confidence: 99%
“…The highly polar aprotic solvent (ACN) is suitable for preparing of CIP imprinted polymers. 19,24 In contrast, the polar protic solvent (methanol) reduces the imprinted polymer selectivity due to their competitive interaction with MAA via hydrogen bond. 19 Moreover, the MIPs synthesized in highly polar solvents have small particles (<2 mm) for SPE applications.…”
Section: Synthesis Of Imprinted Polymersmentioning
confidence: 99%
“…DGTs have been successfully applied to measure trace components in situ in aquatic environments, especially to monitor trace contaminants with high water solubility. Since Chen et al applied DGT to detect the sulfonamide antibiotic in water in 2012, DGT has been gradually developed for the detection of various organic substances in aquatic environment. To date, DGT has been applied to detect pharmaceuticals, , antibiotics, estrogen, anionic pesticides, illicit drugs, , and organophosphate esters . Guo et al confirmed that DGTs can be used for in situ monitoring of several illicit drugs, including METH, in waste waters and rivers .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, research and development of DGT for organic chemicals only started in 2012, but it has already attracted considerable interest and is developing rapidly . To date, sampler development and testing of 136 organic compounds has been reported in the literature (a few from personal communication), with more being conducted. Compound classes include pharmaceuticals and personal care products, illicit drugs, endocrine-disrupting chemicals and pesticides, etc. Table S1 summarizes these publications.…”
mentioning
confidence: 99%